Unfamiliar contexts compared to familiar contexts impair learning in humans - Alizadeh Asfestani, Marjan; Nagel, Juliane; Beer, Sina; Nikpourian, Ghazaleh; Born, Jan; Feld, Gordon Benedikt (Collabra: Psychology, 2023)
Re-exposure to the context that information was learned in facilitates its memory retrieval. However, the influence of context changes on the ability to learn new information is less well understood, which the present work investigated in two experiments with healthy participants (n = 40 per experiment; 20 female). In experiment 1, participants learned a list of word-pairs (A-B) in the morning, after which their memory for the word-pairs was immediately tested. In the evening, they learned and were tested on a second non-overlapping list (C-D), either in the same context or in a different context than the first list (between-subjects). We found that new learning is enhanced in the same context, and that new learning in the other context was decreased compared to baseline. In experiment 2, participants were exposed to both contexts in the morning, but only learned word-pairs in one of them. In the second learning session in the evening, this familiarization with the other context abolished differences between the same and other context group. These data point to context novelty interfering with new learning rather than context familiarity enhancing it. Importantly, the reduction of new learning in the other context in the first experiment, where the context was unfamiliar in both learning sessions, suggests mechanisms beyond attention processes that are bound by the novelty of the other context. Rather, the old context impairs the processing of the new context, possibly by biasing pattern completion and pattern separation trade-offs within the hippocampus.